2020
DOI: 10.1080/17453674.2020.1733375
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fast-track programs on patient-reported outcomes in total hip and knee replacement (THR/TKR) at Swedish hospitals 2011–2015: an observational study including 51,169 THR and 8,393 TKR operations

Abstract: Background and purpose — Fast-track care programs have been broadly introduced at Swedish hospitals in elective total hip and knee replacement (THR/TKR). We studied the influence of fast-track programs on patient-reported outcomes (PROs) 1 year after surgery, by exploring outcome measures registered in the Swedish arthroplasty registers. Patients and methods — Data were obtained from the Swedish Knee and Hip Arthroplasty Registers and included TKR and THR operations 2011–2015 on patients with osteoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 44 publications
(51 reference statements)
0
17
0
1
Order By: Relevance
“…Like other trials 7,12,13 , we did not nd any difference between groups on PROMs 9 months or later after surgery. Berg et al 10 did discover slightly better PROMs in its fast-track cohort at 1 year. However, this difference was not clinically signi cant and multiple cofounders might explain their results, thus limiting the validity of their ndings.…”
Section: Functional Recovery and Promsmentioning
confidence: 95%
See 2 more Smart Citations
“…Like other trials 7,12,13 , we did not nd any difference between groups on PROMs 9 months or later after surgery. Berg et al 10 did discover slightly better PROMs in its fast-track cohort at 1 year. However, this difference was not clinically signi cant and multiple cofounders might explain their results, thus limiting the validity of their ndings.…”
Section: Functional Recovery and Promsmentioning
confidence: 95%
“…To our knowledge, no other studies reported lasting effects of ERAS procedures regarding the time needed to regain important functional abilities. Yet, some studies did nd better PROMs in the rst few months, 9,10,11 supporting the possible superiority of ERAS interventions on recovery in the acute and subacute postoperative period. However, the bene ts of ERAS procedures seemed to vanish with time.…”
Section: Functional Recovery and Promsmentioning
confidence: 98%
See 1 more Smart Citation
“… Inclusion Criteria . (1) Age: 45–75 years; (2) Meets the relevant criteria of postoperative gastrointestinal dysfunction and “PI syndrome” (postinfectious irritable bowel syndrome) in the Guiding Principles for Clinical Research on New Drugs of Traditional Chinese Medicine [ 7 ]; (3) patients without surgical taboo; (4) patients with no abnormal blood test and liver and kidney function; (5) patients who signed informed consent and knew about the content of the study Exclusion Criteria . (1) Patients with previous gastrointestinal diseases; (2) recently taking drugs promoting gastrointestinal motility and drugs affecting electrolyte metabolism things; (3) autoimmune diseases that affect gastrointestinal motility, such as immunodeficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion Criteria . (1) Age: 45–75 years; (2) Meets the relevant criteria of postoperative gastrointestinal dysfunction and “PI syndrome” (postinfectious irritable bowel syndrome) in the Guiding Principles for Clinical Research on New Drugs of Traditional Chinese Medicine [ 7 ]; (3) patients without surgical taboo; (4) patients with no abnormal blood test and liver and kidney function; (5) patients who signed informed consent and knew about the content of the study…”
Section: Methodsmentioning
confidence: 99%